2018
DOI: 10.1097/mao.0000000000001665
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interexaminer Variability of Two Separate Video Head Impulse Test Systems Assessing All Six Semicircular Canals

Abstract: Horizontal SCC testing: both v-HIT systems displayed good intra- and interexaminer variability. Vertical SCC testing: System B displayed good intra- and interexaminer variability whereas the opposite was true with system A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Similarly, VOR gain improvements with HME (80% in patient 1 and 20% in patient 2) seem meaningful. They exceed minimal detectable change (MDC) suggested by studies in healthy subjects with MDC values ranging from 11% [repeatability coefficient of 0.1 and average VOR gain of 0.94, ( 18 )] to 14% [95% limits of agreement of 0.14 and average VOR gain of 1.06, ( 19 )].…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, VOR gain improvements with HME (80% in patient 1 and 20% in patient 2) seem meaningful. They exceed minimal detectable change (MDC) suggested by studies in healthy subjects with MDC values ranging from 11% [repeatability coefficient of 0.1 and average VOR gain of 0.94, ( 18 )] to 14% [95% limits of agreement of 0.14 and average VOR gain of 1.06, ( 19 )].…”
Section: Discussionmentioning
confidence: 64%
“…It is recommended to use precise and uniform criteria defining pathological saccades. Until a consensus is reached on this matter, application of the four standard criteria, defined in a recent study 14 , is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Definition of clinical skills, previous experience, and specific requirements/qualifications need to be clearly defined for both clinical use and research purposes before optimal use of the vHIT test is possible. A recent study indicated that some level of prior experience is beneficial when performing the vHIT; therefore, it is recommended that future examiners undergo systematic training before performing vHIT in a clinical setting 14 . The vHIT test is not just a "plug and play" test; however, if performed correctly, it offers excellent objective diagnostics of vestibular system functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study testing 2 separate vHIT systems revealed some level of interexaminer variability between 2 examiners when using the EyeSeeCam system for examination [13]. The authors therefore conclude that some level of experience is beneficial when performing the vHIT examination with this vHIT system.…”
Section: Resultsmentioning
confidence: 92%